Assessment of Matrix Metalloproteinases a Prognostic Indicator in Advanced Fibrotic Lung Disease: A Systematic Review - Mehvish Aqil; Saif Ur Rahman; Muhammad Zeeshan Aslam; Mostafa Ahmed Abdellah Ahmed; Ammar Ahmed; Sidra Javaid; Ehsan Ul Haq (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Fibrotic lung diseases were seen to have devastating effects among patients globally. Matrix metalloproteinases (MMP) including MMP-7, MMP-9, and MMP-1 have become promising biomarkers for idiopathic pulmonary fibrosis (IPF), and other fibrotic lung diseases. In this systematic review, the objective was to evaluate their roles in predicting disease severity, progression, and response to treatment to increase diagnostic and prognostic accuracy.